A method for preparing multi-level porous ceramics by hydrolysis self-foaming-gel integration
Through the integrated hydrolysis self-foaming-gel preparation method, secondary aluminum ash and other silicon-aluminum raw materials, combined with gel injection molding technology, the problems of secondary aluminum ash disposal and porous ceramic pore structure control are solved, and the problem of secondary aluminum ash disposal and porous ceramic pore structure control is realized. Preparation of high-performance multi-stage pore ceramics and resource utilization of solid waste.
Patent Information
- Application Number
- CN202310353193.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-04-04
AI Technical Summary
The disposal method of secondary aluminum ash mainly relies on storage and landfill, resulting in environmental pollution and waste of resources. It is difficult for the existing technology to effectively control the pore structure and performance of porous ceramics.
Using the integrated hydrolysis self-foaming-gel preparation method, the formation of multi-stage pore structures is achieved through hydrolysis reaction and high-temperature oxidation reaction, and the gel injection is carried out through gel injection. Molding technology achieves high strength and high precision ceramic molding.
The harmless disposal and high-value utilization of hazardous solid waste have been achieved, and multi-stage pore ceramics with excellent performance have been prepared, including high strength, versatility and good environmental adaptability.
Smart Images

Figure CN116444250B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of green disposal and resource utilization of solid waste, and specifically relates to a method for preparing multi-level porous ceramics by hydrolysis self-foaming-gel integration, so as to prepare multi-level porous ceramics with uniform and controllable pore structure. Background Art
[0002] Aluminum ash is a solid waste generated during the production, consumption and reuse of non-ferrous aluminum. With the continuous expansion of the production scale of my country's aluminum industry and the continuous increase in aluminum production, the amount of aluminum ash generated is also increasing. At present, most production companies only recycle primary aluminum ash with a high content of metallic aluminum. The disposal methods of secondary aluminum ash are mainly stockpiling and landfilling. Since secondary aluminum ash contains a large amount of active components such as AlN, metallic Al and heavy metal salts, a large amount of stacking and landfilling will cause serious damage to the natural environment, and waste land resources and the available resources contained in the secondary aluminum ash itself. Realizing the resource utilization of secondary aluminum ash is an urgent problem to be solved.
[0003] Porous ceramics have low density, high specific surface area, excellent chemical and thermal stability, good sound absorption / heat insulation / biocompatibility / wear and corrosion resistance, and are widely used as thermal insulation materials, filter materials, sound absorption materials, catalyst carriers and bio-scaffolds. Porous ceramics are often made from natural minerals such as kaolin and feldspar, or high-purity powders such as Al2O3, AlN, SiC, SiO2, and hydroxyapatite. Inorganic solid waste has become an important secondary resource for the preparation of porous ceramics because it contains a large amount of silicate components. Compared with porous ceramics with a single pore structure, the multi-level pore structure can enable the material to better play the functions of multiple pores under the same volume conditions, and obtain higher permeability, specific surface area, mechanical properties and lower volume density and other excellent properties.
[0004] Chinese patent CN113735611A discloses a method for preparing low-shrinkage porous ceramics by high-temperature foaming of aluminum ash slag, wherein the secondary aluminum ash slag is first subjected to spray granulation, dry pressing, and high-temperature sintering to finally obtain a low-shrinkage porous ceramic material. However, the molding method of the invention is dry pressing, which can only be used to prepare ceramic components with simple shapes, and the pore structure is a single pore structure obtained by high-temperature oxidation and foaming of the Al-containing active component in the secondary aluminum ash slag.
[0005] Chinese patent CN113563102A discloses a method for preparing porous ceramics by in-situ solidification molding of aluminum ash water-based slurry. First, aluminum ash, ceramic powder, dispersant, binder, sintering aid and water are evenly mixed to obtain a solid-liquid mixed phase slurry. The slurry is then injection molded and heated. The aluminum-containing active ingredient is hydrolyzed, foamed and solidified. After molding, the porous ceramics are demolded, dried and sintered. The main molding method of this invention is to hydrolyze the high solid content secondary aluminum ash water-based slurry to produce an aluminum hydroxide network to fix the ceramic particles therein. The method provided by this patent will produce aluminum hydroxide and gas at the same time due to the room temperature hydrolysis reaction, that is, it determines the molding and foaming processes at the same time, making the foaming process difficult to control and the pore structure difficult to effectively regulate at this stage.
[0006] Chinese patent CN109970456A discloses a method for recycling and reusing aluminum ash slag, which first separates iron impurities and metallic aluminum from the aluminum ash slag, washes it to remove aluminum nitride and salts, and then mixes it with kaolin, bentonite and talc for wet grinding and slurrying, and then adds stabilizers and surfactants, and obtains foam ceramics after slurry hanging, drying, debinding and sintering. The molding process in this invention is an organic foam impregnation method, and the pore structure comes from the organic foam template. The aluminum ash slag needs to be washed for pretreatment to remove salt and nitrogen, which increases the production cost, and there is no secondary foaming during high-temperature sintering.
[0007] Chinese patent CN104402456A discloses a method for forming porous ceramics by foaming injection molding gel, first preparing weakly acidic water-based slurry A and water-based slurry B containing carbonates; after degassing the slurry, adding initiators, catalysts, and surfactants, mixing slurries A and B and stirring to foam, and obtaining porous ceramics through injection molding, gel curing, demolding, drying, sintering and other process processes. The organic monomer in the invention is selected from acrylamide or methacrylamide, and the cross-linking agent is selected from methylene bisacrylamide or polyethylene glycol dimethacrylate, which has neurotoxicity. The foaming method of the invention is achieved by carbonate decomposition reaction combined with mechanical stirring to introduce air. Summary of the invention
[0008] In view of the above problems, the present invention provides a method for preparing multi-level porous ceramics by hydrolysis self-foaming-gel integration. The method uses secondary aluminum ash as the main raw material, foaming agent and curing agent, assisted by environmentally friendly gel injection molding, to integrate the foaming and curing processes and prepare a porous green body, which is further sintered at high temperature to obtain lightweight multi-level porous ceramics.
[0009] The technical solution adopted by the present invention is:
[0010] A method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0011] The secondary aluminum ash after pretreatment is mixed with other silicon-aluminum raw materials, and a dispersant, a binder, a sintering aid and water are added, and the mixture is uniformly mixed to obtain a water-based suspension, and the water-based suspension is heated to a certain temperature; the gel material is dissolved at a certain temperature, and added to the heated water-based suspension and stirred uniformly to obtain a mixed suspension; and then injection molding, foaming and curing, demoulding, drying, debinding, and sintering are performed;
[0012] During the foaming and curing process, the Al-containing active components in the secondary aluminum ash undergo a hydrolysis reaction to generate gas and aluminum hydroxide sol; at the same time, the organic monomers of the gel material undergo a polymerization reaction to form a three-dimensional gel network, which acts as a curing agent. The three-dimensional gel network fixes the solid raw material particles (the solid raw material particles include the secondary aluminum ash and other aluminum-silica raw materials) and the gas, and realizes hydrolysis foaming and rapid molding at room temperature.
[0013] The debinding and sintering steps are performed in an air environment at high temperature. During the debinding and sintering steps, the unhydrolyzed Al-containing active components in the green body undergo oxidation reactions to generate gas to achieve high-temperature foaming.
[0014] Furthermore, the components of the secondary aluminum ash include Al-containing active components and other components:
[0015] The Al-containing active components in the secondary aluminum ash include:
[0016] AlN and elemental aluminum; or
[0017] AlN and elemental aluminum and one or more of Al4C3, AlP, and Al2S3.
[0018] The other components include: one or more of Al2O3, MgAl2O4, Si, SiO2, CaO, MgO, TiO2, Fe2O3, Na3AlF6, NaCl, KCl, NaAlCl4, and KAlCl4.
[0019] The hydrolysis reaction of the Al-containing active component includes but is not limited to the following reactions:
[0020] AlN+3H2O→AlOOH+NH3↑
[0021] NH3+H2O→NH4 + +OH -
[0022] AlOOH+H2O→Al(OH)3
[0023] 2Al+6H2O→2Al(OH)3+3H2↑
[0024] AlP+3H2O→Al(OH)3+PH3↑
[0025] Al2S3+6H2O→2Al(OH)3+3H2S↑
[0026] Al4C3+12H2O→4Al(OH)3+3CH4↑
[0027] Al(OH)3→Al2O3+3H2O
[0028] 4AlN+5O2→2Al2O3+4NO↑
[0029] 4Al+3O2→2Al2O3
[0030] Si+O2→SiO2;
[0031] Furthermore, the method for pretreating the secondary aluminum ash is: ball milling and sieving the secondary aluminum ash to obtain secondary aluminum ash with an average particle size of 1-30 μm; wherein the ball milling adopts a planetary ball mill, the ball milling time is 0.5h~48h, the ball milling speed is 50-300r / min, and the ball milling process is dry grinding or wet grinding using alcohol as an auxiliary agent.
[0032] Further, the other silica-alumina raw materials include: one or more of clay, natural sand, feldspar, alumina, quartz, zirconia, fly ash, coal gangue, kaolin, clay, tailings, metallurgical slag, waste glass or other silica-alumina waste slag;
[0033] The dispersant includes one or more of ammonium citrate, ammonium polyacrylate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide;
[0034] The binder includes one or more of polyethylene glycol, polyvinyl alcohol, sodium pyrophosphate, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose, and polyvinyl pyrrolidone;
[0035] The sintering aid includes one or more of CaO, MgO, SiO2, TiO2, V2O5, MnO, Y2O3, Sc2O3, Lu2O3, H3BO3, and B.
[0036] Further, the content of the solid raw material in the water-based suspension is 20-80wt.%, and the solid raw material is a mixture of the secondary aluminum ash and the other aluminum-silica raw materials; wherein the secondary aluminum ash accounts for 10-100wt.% of the total amount of the solid raw material, and the total mass is 100wt.%, and the remainder is other aluminum-silica raw materials;
[0037] The amount of the dispersant added is 0.01-10wt.% of the total amount of the solid raw material;
[0038] The amount of the binder added is 0.01-10wt.% of the total amount of the solid raw material;
[0039] The added amount of the sintering aid accounts for 0.01-10wt.% of the total amount of the solid raw material.
[0040] Furthermore, the gel material is an environmentally friendly gel material, which is dissolved at a certain temperature, added to the heated water-based suspension and stirred evenly, and the specific method is as follows:
[0041] The water-based suspension is heated to 30-95° C.; the gel powder of the environmentally friendly gel material is mixed with water 10-50 times the weight of the gel powder, heated and stirred to prepare a sol at 40-95° C.; the sol is added to the heated water-based suspension and stirred evenly;
[0042] Wherein, the environmentally friendly gel material includes one or more of gelatin, pectin, agarose gel, carrageenan, and konjac gum;
[0043] The mass of the added gel powder accounts for 0.1-10wt.% of the total amount of the solid raw materials, and the foaming degree of the secondary aluminum ash is controlled by controlling the heating temperature of the water-based suspension. The higher the temperature of the water-based suspension, the more intense the foaming of the secondary aluminum ash during the condensation process after adding the gel.
[0044] Among them, the environmentally friendly gel material and the aluminum-containing active component are hydrolyzed to produce AlOOH gel which acts as a curing agent.
[0045] Furthermore, the injection molding, foaming and curing, demoulding, drying, debinding and sintering are specifically:
[0046] The mixed suspension after adding the gel is injected into a mold made of a non-permeable material for foaming and curing; after curing, the wet gel blank is taken out from the mold, and a porous blank of a desired shape is obtained after drying; the completely dried porous blank is debinded under high-temperature air conditions, and further sintered at high temperature to obtain multi-level porous ceramics.
[0047] Furthermore, the mixed suspension is foamed and cured in the mold for 5-60 minutes; and the wet gel blank is dried at 25-90° C. for 10 minutes to 14 days.
[0048] Furthermore, the temperature during the debinding process is 400-700°C and the temperature is kept for 5min-10h;
[0049] The sintering temperature during the high temperature sintering process is 800-1900° C. and the temperature is kept for 5 minutes to 24 hours.
[0050] Furthermore, the porosity of the obtained multi-level porous ceramic is 20%-95%; the hydrolysis foaming process produces macropores with an average pore size of 50μm-2mm, and the high-temperature foaming process produces micropores with an average pore size of 0.1-50μm.
[0051] Compared with the prior art, the method of the present invention has the following advantages:
[0052] (1) The method of the present invention utilizes the reaction characteristics of secondary aluminum ash, combined with gel injection molding technology to prepare high-strength porous green bodies, and further removes binders and sintering to obtain high-performance multi-level porous ceramics, thereby realizing the harmless disposal and high-value utilization of hazardous solid waste. Among them, the present invention utilizes the hydrolysis characteristics and high-temperature oxidation characteristics of secondary aluminum ash to realize two foamings (hydrolysis foaming and high-temperature foaming) during the curing and sintering process, and the aluminum hydroxide sol produced by the hydrolysis foaming at room temperature can synergize with the gel material to quickly form a three-dimensional network skeleton, realize the in-situ curing of ceramic particles and the rapid formation of pore structure, and does not require the solid content of the suspension, effectively realizing the molding of porous green bodies with different solid contents with excellent strength.
[0053] (2) The gel material used in the present invention is a non-toxic and environmentally friendly gel, which avoids secondary pollution.
[0054] (3) The ceramic forming method provided by the present invention adopts gel injection molding technology to form ceramic parts with high green body strength, high precision and complex shape, which is beneficial to effectively control the porous structure obtained by hydrolysis and foaming of secondary aluminum ash during the forming stage; it can be widely used in the solidification of various ceramic systems and the preparation of ceramic parts; and in the water bath stage and the sintering stage, pore structures of different scales will be generated to form a multi-level pore structure.
[0055] (4) In the present invention, the secondary aluminum ash not only serves as a raw material, but also plays the role of a foaming agent (hydrolysis and high temperature), thereby realizing the multi-channel application of inorganic solid waste and reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The present invention is a flow chart of a method for preparing multi-level porous ceramics by hydrolysis self-foaming-gel integration.
[0057] Figure 2 This is a SEM image of the fracture of the unsintered ceramic body obtained in Example 1 of the present invention.
[0058] Figure 3 This is a high-magnification SEM image of the fracture of the unsintered ceramic body obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0059] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0060] Example 1
[0061] like Figure 1 As shown, this embodiment provides a method for preparing multi-level porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0062] The secondary aluminum ash was ball-milled in a planetary ball mill for 48 h at a speed of 100 r / min. Alcohol was used as an auxiliary agent for wet milling during the ball-milling process. After ball-milling, the secondary aluminum ash was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 4.17 μm.
[0063] Secondary aluminum ash and fly ash are selected as solid raw materials, the content of secondary aluminum ash in the solid raw materials is 30wt.%, and the content of fly ash is 70wt.%; and 5.0wt.% of the dispersant ammonium citrate, accounting for 0.5wt.% of the solid raw material, the binder polyethylene glycol, accounting for 0.5wt.% of the solid raw material, and the sintering aid Y2O3, accounting for 1.0wt.% of the solid raw material, are added and mixed with water, and ball milled for 30 minutes to obtain a uniform water-based suspension, in which the content of solid raw materials in the water-based suspension is 40wt.%.
[0064] Pectin powder was mixed with 20 times the amount of water, heated and stirred at 70°C until the powder was completely dissolved to prepare pectin sol, and the sol was introduced into a suspension heated to 60°C and mixed and stirred evenly; the mass of the added pectin powder accounted for 1.0wt.% of the solid raw material.
[0065] The suspension after adding gel was injected into the mold and demoulded after curing for 30 minutes; the wet gel blank was dried at 25°C for 14 days ( Figure 2-3 The SEM image of the fracture of the ceramic body that has not been sintered, and the high-magnification SEM image refer to); Figure 2 It can be seen that the unsintered ceramic body has uniformly distributed pores. Figure 3 It can be seen that the surface of the particles is completely attached with flocculent colloids composed of Al(OH)3 and carrageenan; finally, the porous green body is sintered in an air environment at 1200°C for 3 hours to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 54%, wherein the average pore size of the macropores obtained by hydrolysis and foaming is 220μm, and the average pore size of the micropores produced by high-temperature reaction is 15μm.
[0066] Example 2
[0067] This embodiment provides a method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0068] The secondary aluminum ash was ball milled in a planetary ball mill for 48 hours at a speed of 300 r / min. Alcohol was used as an auxiliary agent for wet milling during the ball milling process. After ball milling, it was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 1.03 μm.
[0069] Secondary aluminum ash and coal gangue are selected as solid raw materials, the content of secondary aluminum ash in the solid raw materials is 10wt.%, and the content of coal gangue is 90wt.%; and a mixed sintering aid consisting of dispersant ammonium citrate accounting for 2.0wt.% of the total solid raw material, a binder sodium pyrophosphate accounting for 0.5wt.% of the total solid raw material, Y2O3 accounting for 3.0wt.% of the total solid raw material and silicon powder accounting for 7.0wt.% of the total solid raw material is added, and then mixed with water, ball milled for 30 minutes to obtain a uniform water-based suspension, and the solid raw material content in the water-based suspension is 65wt.%.
[0070] Agarose powder was mixed with 25 times of water, heated and stirred at 70°C until the powder was completely dissolved to prepare agarose sol, and the sol was introduced into a suspension heated to 45°C and mixed and stirred evenly; the mass of the added agarose powder accounted for 3.0wt.% of the total amount of solid raw materials.
[0071] The suspension after adding gel is injected into the mold and demolded after curing for 40 minutes; the wet gel body is dried at 40°C for 3 days; finally, the porous body is sintered in an air environment at 1400°C for 1 hour to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 37%, wherein the average pore size of the macropores obtained by hydrolysis and foaming is 100μm, and the average pore size of the micropores produced by high-temperature reaction is 26μm.
[0072] Example 3
[0073] This embodiment provides a method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0074] The secondary aluminum ash was ball milled for 24 hours in a planetary ball mill with a ball milling speed of 100 r / min. Alcohol was used as an auxiliary agent for wet milling during the ball milling process. After ball milling, it was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 5.03 μm.
[0075] Secondary aluminum ash and light-burned magnesium oxide are selected as solid raw materials, the content of secondary aluminum ash in the solid raw materials is 60wt.%, and the content of light-burned magnesium oxide is 40wt.%; and 1.0wt.% of the dispersant ammonium polyacrylate, 0.3wt.% of the binder sodium carboxymethyl cellulose, and 0.01wt.% of the sintering aid MnO2 accounting for the total amount of solid raw materials are added, and then mixed with water, and ball milled for 30 minutes to obtain a uniform water-based suspension, in which the content of solid raw materials in the water-based suspension is 60wt.%.
[0076] Carrageenan powder was mixed with 30 times the amount of water, heated and stirred at 90°C until the powder was completely dissolved to prepare carrageenan sol, and the sol was introduced into a suspension heated to 80°C and mixed and stirred evenly; the mass of the added carrageenan powder accounted for 0.1wt.% of the total amount of solid raw materials.
[0077] The suspension after adding gel is injected into the mold and demolded after curing for 15 minutes; the wet gel body is dried at 90°C for 10 minutes; finally, the porous body is sintered in an air environment at 1900°C for 5 minutes to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 76%, wherein the average pore size of the macropores obtained by hydrolysis and foaming is 700μm, and the average pore size of the micropores produced by high-temperature reaction is 50μm.
[0078] Example 4
[0079] This embodiment provides a method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0080] The secondary aluminum ash was ball milled in a planetary ball mill for 0.5 h at a speed of 50 r / min. Alcohol was used as an auxiliary agent for wet grinding during the ball milling process. After ball milling, the secondary aluminum ash was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 29.77 μm.
[0081] The solid raw materials include 25wt.% of secondary aluminum ash and 75wt.% of waste ceramic particles; 0.01wt.% of dispersant ammonium polyacrylate, 0.2wt.% of binder sodium carboxyethyl cellulose, and 2.0wt.% of sintering aid V2O5 accounting for the total amount of solid raw materials are added and mixed with water; ball milling is performed for 30 minutes to obtain a uniform water-based suspension, and the solid raw material content in the water-based suspension is 80wt.%.
[0082] Konjac gum powder is mixed with 20 times of water, heated and stirred at 75°C until the powder is completely dissolved to prepare konjac gum sol, and the sol is introduced into a suspension heated to 50°C and mixed and stirred evenly; the mass of the added konjac gum powder accounts for 2.0wt.% of the total mass of the solid raw materials.
[0083] The suspension after adding gel was injected into the mold and demolded after curing for 35 minutes; the wet gel body was dried at 50°C for 1 day; finally, the porous body was sintered in an air environment at 1500°C for 10 hours to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 43%, wherein the average pore size of the macropores obtained by hydrolysis and foaming was 140μm, and the average pore size of the micropores produced by high-temperature reaction was 23μm.
[0084] Example 5
[0085] This embodiment provides a method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0086] The secondary aluminum ash was ball milled in a planetary ball mill for 12 hours at a speed of 60 r / min. Alcohol was used as an auxiliary agent for wet grinding during the ball milling process. After ball milling, the secondary aluminum ash was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 11.46 μm.
[0087] The solid raw material is 100wt.% secondary aluminum ash, and 10.0wt.% of the dispersant tetramethylammonium hydroxide, 10.0wt.% of the binder polyvinyl alcohol, and 5wt.% of the sintering aid SiO2 are added to the total solid raw material. Ball milling is performed for 30 minutes to obtain a uniform water-based suspension, and the solid raw material content in the water-based suspension is 20.0wt.%.
[0088] Carrageenan powder was mixed with 30 times the amount of water, heated and stirred at 95°C until the powder was completely dissolved to prepare carrageenan sol, and the sol was introduced into a suspension heated to 95°C and mixed and stirred evenly; the mass of the added carrageenan powder accounted for 10.0wt.% of the total amount of solid raw materials.
[0089] The suspension after adding gel is injected into the mold and demolded after curing for 5 minutes; the wet gel body is dried at 30°C for 7 days; finally, the porous body is sintered in an air environment at 1300°C for 2 hours to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 95%, wherein the average pore size of the macropores obtained by hydrolysis and foaming is 2mm, and the average pore size of the micropores produced by high-temperature reaction is 17μm.
[0090] Example 6
[0091] This embodiment provides a method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, the method comprising:
[0092] The secondary aluminum ash was ball milled in a planetary ball mill for 24 hours at a speed of 300 r / min. Alcohol was used as an auxiliary agent for wet milling during the ball milling process. After ball milling, it was sieved through a 100-mesh sieve. The average particle size of the obtained secondary aluminum ash was 2.21 μm.
[0093] The solid raw materials selected were 20wt.% secondary aluminum ash, 50wt.% electrolytic manganese slag and 30wt.% fly ash, and 3.0wt.% of dispersant ammonium citrate, 0.3wt.% of binder polyvinyl alcohol, and 3.0wt.% of sintering aid TiO2 accounting for the total amount of solid raw materials were added. The uniform water-based suspension was obtained by ball milling for 30 minutes, and the solid raw material content in the water-based suspension was 50wt.%.
[0094] The gelatin powder was mixed with 10 times the amount of water, heated and stirred at 70°C until the powder was completely dissolved to prepare a gelatin sol, and the sol was introduced into a suspension heated to 30°C and mixed and stirred evenly; the mass of the added gelatin powder accounted for 7.0wt.% of the total amount of solid raw materials.
[0095] The suspension after adding gel is injected into the mold and demolded after curing for 60 minutes; the wet gel body is dried at 40°C for 2 days; finally, the porous body is sintered in an air environment at 800°C for 24 hours to obtain a multi-level porous ceramic with uniform pore distribution and a porosity of 20%, wherein the average pore size of the macropores obtained by hydrolysis and foaming is 50μm, and the average pore size of the micropores produced by high-temperature reaction is 0.1μm.
[0096] The amount of secondary aluminum ash added to the raw material was studied, and the amount of secondary aluminum ash added was set to 20%, 30%, 40%, and 50%, respectively. The other parameters were the same as in Example 1, and the results were shown in Table 1. Due to the increase in the amount of secondary aluminum ash added, the amount of gas generated during the hydrolysis and sintering processes increased, and the porosity, macropore size, and micropore size of the product all showed an increasing trend.
[0097] Table 1 Product performance changes with different secondary aluminum ash contents
[0098] Secondary aluminum ash Fly ash Porosity Macropore size / μm Micropore size / μm 20% 80% 47% 180 12 30% 70% 54% 220 15 40% 60% 62% 300 23 50% 50% 68% 420 31
[0099] The mixing temperature of the water-based slurry and the gel material was studied, and the mixing temperature was set to 30°C, 40°C, and 50°C, respectively. The other parameters were the same as those in Example 4, and the results were shown in Table 2. As the mixing temperature increased, the hydrolysis rate increased, and the porosity and macroscopic size of the product increased. However, the remaining aluminum-containing active components decreased during the sintering stage, and the micropore size tended to decrease.
[0100] Table 2 Product performance changes at different mixing temperatures
[0101] Mixing temperature Porosity Macropore size / μm Micropore size / μm 30℃ 31% 60 32 40℃ 37% 100 27 50℃ 43% 140 23 60℃ 49% 200 21
[0102] The sintering temperature was studied, and the sintering temperatures were set to 1200°C, 1300°C, 1400°C, and 1500°C respectively. The other parameters were the same as those in Example 2, and the results were shown in Table 3. As the sintering temperature increased, the liquid phase viscosity in the green body decreased, and the macropores generated in the hydrolysis stage were filled to a certain extent, and the size was slightly reduced. However, due to the decrease in liquid phase viscosity and the intensification of the foaming reaction, the pressure in the bubbles increased, the bubbles expanded, and the micropores tended to increase until the temperature exceeded 1400°C and over-burning occurred. The liquid phase viscosity was too low, the gas escaped, and the micropore size also decreased accordingly.
[0103] Table 3 Product performance changes at different sintering temperatures
[0104] Sintering temperature Porosity Macropore size / μm Micropore size / μm 1200℃ 35% 101 21 1300℃ 37% 100 26 1400℃ 38% 98 29 1500℃ 36% 90 28
[0105] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration, characterized in that: The method comprises: The method for pre-treating the secondary aluminum ash is: ball milling and sieving the secondary aluminum ash to obtain secondary aluminum ash with an average particle size of 1-30 μm; The secondary aluminum ash after pretreatment is mixed with other silicon-aluminum raw materials, and a dispersant, a binder, a sintering aid and water are added, and the mixture is uniformly mixed to obtain a water-based suspension, and the water-based suspension is heated to a certain temperature; the gel material is dissolved at a certain temperature, added to the heated water-based suspension and stirred uniformly to obtain a mixed suspension; and then injection molding, foaming and curing, demoulding, drying, debinding and sintering are performed; wherein, The gel material is an environmentally friendly gel material, which is dissolved at a certain temperature, added to the heated water-based suspension and stirred evenly. The specific method is as follows: The water-based suspension is heated to 30-95° C.; the gel powder of the environmentally friendly gel material is mixed with water 10-50 times the weight of the gel powder, heated and stirred to prepare a sol at 40-95° C.; the sol is added to the heated water-based suspension and stirred evenly; The mixed suspension after adding the gel is injected into a mold made of a water-impermeable material for foaming and curing; after curing, the wet gel body is taken out from the mold, and a porous body of a desired shape is obtained after drying; the completely dried porous body is debinded under air conditions, and further sintered at a high temperature to obtain a multi-level porous ceramic; the time for the mixed suspension to foam and cure in the mold is 5-60 minutes; The environmentally friendly gel material comprises one or more of gelatin, pectin, agarose gel, carrageenan and konjac gum; the solid raw material is a mixture of the secondary aluminum ash and other aluminum-silica raw materials, the mass of the added gel powder accounts for 0.1-10wt.% of the total amount of the solid raw materials, and the foaming degree of the secondary aluminum ash is controlled by controlling the heating temperature of the water-based suspension; During the foaming and curing process, the Al-containing active components in the secondary aluminum ash undergo a hydrolysis reaction to generate gas and aluminum hydroxide sol; at the same time, the organic monomers of the gel material undergo a polymerization reaction to form a three-dimensional gel network, which acts as a curing agent. The three-dimensional gel network fixes the solid raw material particles and the gas, and realizes hydrolysis foaming and rapid molding at room temperature; the Al-containing active components in the secondary aluminum ash include: AlN and elemental aluminum and one or more of Al4C3, AlP, and Al2S3; The debinding and sintering steps are performed in an air environment at a high temperature, wherein the unhydrolyzed Al-containing active components in the green body undergo oxidation reaction to generate gas to achieve high-temperature foaming; The porosity of the obtained multi-level porous ceramic is 20%-95%; the hydrolysis foaming process produces macropores with an average pore size of 50μm-2mm, and the high-temperature foaming process produces micropores with an average pore size of 0.1-50μm.
2. The method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration according to claim 1, characterized in that: The ball milling adopts a planetary ball mill, the ball milling time is 0.5h~48h, the ball milling speed is 50-300r / min, and the ball milling process is dry grinding or wet grinding using alcohol as an auxiliary agent.
3. The method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration according to claim 1, characterized in that: The other silicon-alumina raw materials include: one or more of natural sand, feldspar, alumina, quartz, fly ash, coal gangue, kaolin, tailings, metallurgical slag, waste glass or other silicon-alumina waste slag; The dispersant includes one or more of ammonium citrate, ammonium polyacrylate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide; The binder includes one or more of polyethylene glycol, polyvinyl alcohol, sodium pyrophosphate, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose, and polyvinyl pyrrolidone; The sintering aid includes one or more of CaO, MgO, SiO2, TiO2, V2O5, MnO, Y2O3, Sc2O3, Lu2O3, H3BO3, and B.
4. The method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration according to claim 1, characterized in that: The content of solid raw materials in the water-based suspension is 20-80wt.%, wherein the secondary aluminum ash accounts for 10-100wt.% of the total amount of the solid raw materials, and the total mass is 100wt.%, and the remainder is other aluminum-silicon raw materials; The amount of the dispersant added is 0.01-10wt.% of the total amount of the solid raw material; The amount of the binder added is 0.01-10wt.% of the total amount of the solid raw material; The added amount of the sintering aid accounts for 0.01-10wt.% of the total amount of the solid raw material.
5. The method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration according to claim 1, characterized in that: The wet gel body is dried at 25-90° C. for 10 min-14 days.
6. The method for preparing hierarchical porous ceramics by hydrolysis self-foaming-gel integration according to claim 1, characterized in that: The temperature during the debinding process is 400-700°C and the temperature is kept for 5min-10h; The sintering temperature during the high temperature sintering process is 800-1900° C. and the temperature is kept for 5 minutes to 24 hours.
Citation Information
Patent Citations
Self-foaming injection-molding gel-forming porous ceramic preparation method
CN104402456A
Aluminum ash recovering and reutilizing method
CN109970456A
Method for preparing low-shrinkage porous ceramic through high-temperature self-foaming of aluminum ash
CN113735611A
Method for preparing porous ceramic by in-situ curing molding of water-based slurry containing aluminum ash
CN113563102A
Hydrogel-based metal slurry and preparation method thereof
CN114226717A